Pengaruh Ekstrak Jintan Hitam Terhadap Berat Badan dan Jalur NF-κB Tikus Wistar dengan Mukositis Oral Akibat Cisplatin: Studi in Vivo – in Silico - ⁠Oke Kadarullah; Hasna Khalifatunnisa; ⁠Muhammad Fadhol Romdhoni; Titik Kusumawinakhyu (Universitas Tidar, 2026)
Cisplatin-induced oral mucositis involves oxidative stress and inflammatory pathway activation thatcontribute to weight loss. Nigella sativa contains thymoquinone with antioxidant and anti-inflammatoryproperties, yet integrative evidence linking in vivo effects and in silico molecular affinity remains limited.Standard in vivo therapy commonly uses N-acetylcysteine (NAC). This study evaluated the effect of Nigellasativa extract on body weight changes and the NF-κB inflammatory pathway in Wistar rats with cisplatininducedoral mucositis using in vivo and in silico approaches.Thirty rats were divided into five groups: negativecontrol, Nigella sativa at 125, 250, and 500 mg/kgBW, and NAC 100 mg/kgBW as positive control. Body weightwas measured before and after induction and analyzed using Repeated ANOVA. Molecular docking ofthymoquinone and NAC to NF-κB was conducted for in silico analysis. A significant difference was observedbetween pre- and post-treatment body weight (F=143.399; p<0.001). Mean weight decreased from 247.30 g to216.83 g (−30.47 g). The control group showed the greatest loss (−53.84 g), while the 125 mg/kgBW doseprovided the best protection (−20.33 g). Thymoquinone demonstrated stronger binding af????inity (−5.2kcal/mol) than NAC (−4.2 kcal/mol). Nigella sativa, particularly at 125 mg/kgBW, effectively reduced weightloss and may suppress NF-κB activation. Keywords: Cisplatin, Mucositis Oral, NF-κB, Nigella Sativa, Thymoquinone.